Pengaruh pH terhadap Koagulasi Mikroplastik Polyethylene Terephthalate (PET) menggunakan Kitosan dari Cangkang Kepiting (Scylla serrata) - Haflatul HudaAli; Indang Dewata (Lembaga Yasin AlSys, 2025)
Polyethylene Terephthalate (PET) microplastics are among the primary contaminants in aquatic environments and pose potential risks to human health. Coagulation is an effective method for reducing microplastics; however, conventional coagulants such as alum may leave harmful residues. This study aims to evaluate the effectiveness of chitosan synthesized from crab shell waste (Scylla serrata) as an eco-friendly biocoagulant in the coagulation of PET microplastics. Chitosan synthesis was carried out through three stages: demineralization, deproteinization, and deacetylation. The coagulation process was conducted under varying pH conditions (3, 5, 7, 9, and 11), with a chitosan dosage of 500 mg/L and a sedimentation time of 45 minutes. The results show that optimal conditions were achieved at pH 7, with microplastic removal efficiency reaching 98.4%. Characterization using Fourier Transform Infrared Spectroscopy (FTIR), Particle Size Analyzer (PSA), and stereo microscopy confirmed successful floc formation and active interaction between chitosan and microplastics. The study concludes that chitosan derived from crab shell waste has strong potential as an effective and environmentally friendly alternative coagulant for treating water contaminated with microplastics.